2020
DOI: 10.21203/rs.3.rs-56408/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel four-gene prognostic signature as a risk biomarker in cervical cancer

Abstract: Background: Cervical cancer (CC) is a major malignancy affecting women worldwide, with limited treatment options for patients with advanced disease. The aim of this study was to identify novel prognostic biomarkers for CC by a bioinformatics-based analysis using the Gene Expression Omnibus (GEO) database and The Cancer Genome Atlas (TCGA)-CC cohort. Methods: RNA-Seq data from four GEO datasets (GSE5787, GSE6791, GSE26511, and GSE63514) were used to identify differentially expressed genes (DEGs) between CC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Roszik et al 38 revealed MMP-1 was overexpressed in cervical cancer, and knockdown of MMP-1 reduced the proliferation and migration of cervical cancers. Wang et al 39 proposed MMP-1 as a risk factor in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roszik et al 38 revealed MMP-1 was overexpressed in cervical cancer, and knockdown of MMP-1 reduced the proliferation and migration of cervical cancers. Wang et al 39 proposed MMP-1 as a risk factor in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we carried out this meta-analysis to evaluate the correlation between MMPs and prognosis in cervical cancer. 25-41…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan Meier Plotter was utilized to determine the prognostic values of IGF1, BIRC5, VEGF, and MMP1, which showed that increased IGF1 or BIRC5 expression correlated with better survival, while increased VEGF or MMP1 expression correlated with poorer survival in cervical carcinoma patients (Supplementary Material). Previous studies have consistently reported [14][15][16][17][18] that VEGF, MMP1 and BIRC5 gene expression is up-regulated and IGF1 expression is down-regulated in both cervical and vulvar tumors. We also performed follow-up and survival analyses, which showed that the 4 genes had statistically insignificant prognostic value in VSCC, which may be due to the insufficient sample size and the short follow-up time of some cases.…”
Section: Discussionmentioning
confidence: 99%